Construction of layered structures on valve metal alloys by microplasma oxidation - Baranova, Tatiana A.; Mamaev, A. I.; Mamaeva, V. A.; Kovalskaya, Ya. B.; Chubenko, A. K. (IOP Conference Series: Materials Science and Engineering)
Process of layered structure materials creation based on aluminum alloys is presented. Microplasma texturing method, microplasma oxidation method and chemical metallization method were used to create these structures. Non-conductive nonmetallic inorganic coatings were produced by microplasma oxidation method. Obtained structures showed high durability under thermal stress loads due to substrate metal - non-conductive nonmetallic inorganic coating phase boundary texturing.